Total Rainbow Connection Number of Some Graph Operations - Hengzhe Li; Yingbin Ma; Yan Zhao (Axioms, 2022)
In a graph H with a total coloring, a path Q is a total rainbow if all elements in <semantics>V(Q)∪E(Q)</semantics>, except for its end vertices, are assigned different colors. The total coloring of a graph H is a total rainbow connected coloring if, for any <semantics>x,y∈V(H)</semantics>, there is a total rainbow path joining them. The total rainbow connection number <semantics>trc(H)</semantics> of H is the minimum integer r such that there is a total rainbow-connected coloring of H using r colors. In this paper, we study the total rainbow connection number of several graph operations (specifically, adding an edge, deleting an edge, and the Cartesian product) for which the total rainbow connection number is upper-bounded by a linear function of its radius.